Avaliação da qualidade e do consumo energético no processo de secagem intermitente em sementes de soja - Bissaro, Camila Andressa (2018)
Seed drying constitutes an essential operation in the soybean production chain, promoting a reduction in the humidity of the product to a safe level of storage. Contrary to conventional operation, intermittent drying operates under transient conditions during the drying process, besides being an alternative operation that aims to improve the process in terms of yield, energy expenditure and quality of dry material. In this context, soybean seed (Monsoy 6410 IPRO) drying experiments were performed in conventional and intermittent fixed bed thin layer, comparing them in relation to the kinetic behavior, in terms of the adjustment of the experimental data with empirical mathematical models, and analysis of the energy consumption of the operations. Furthermore, the physiological quality of dried soybean seeds were evaluated in terms of germination, vigour (seedling length) and fissure. Drying air temperatures of 50°C and 70°C in both operations were used, however, intermittent drying consisted in modulating the temperature and feed rate over a specific period and amplitude, subjecting the seeds (50 and 70 °C) at regular intervals (5, 10 and 15 min), interspersed with seed withdrawal and exposure to the environment (30 °C) without air circulation during the same time interval, successively, until the seeds reach a defined storage humidity of 12% (d.b).The effective drying time was reduced under intermittent operation, as well as greater preservation in the quality of the dried material, directly influencing the better physiological performance of the seeds in relation to the conventional operation, except for the high temperature of the drying air (70°C). Moreover, the modulation performed in the intermittent process significantly reduced the energy consumption of soybean drying process